Pediatric immune myelofibrosis (PedIMF) as a novel and distinct clinical pathological entity - Guerra, Fabiola; L’Imperio, Vincenzo; Bonanomi, Sonia; Spinelli, Marco; Coliva, Tiziana Angela; Dell’Acqua, Fabiola; Ferrari, Giulia Maria; Corti, Paola; Balduzzi, Adriana; Biondi, Andrea; Pagni, Fabio; Saettini, Francesco (Frontiers in Pediatrics, 2022)
Myelofibrosis is a rare myeloproliferative disorder. The detailed descriptions of myelofibrosis in children and adolescents is limited to a few case series and case reports describing fewer than 100 patients, thus suggesting the extreme rarity of this condition prior to adulthood. Though pediatric patients rarely present the typical features and outcomes usually observed in older people, pediatric myelofibrosis is not considered an independent entity. Here we aim to describe patients with pediatric myelofibrosis, showing different clinical and pathological features when compared to the World Health Organization 2016 Primary Myelofibrosis classification. We retrospectively collected and analyzed 14 consecutive pediatric myelofibrosis diagnosed in our Pediatric hematology outpatient clinic over a six-year period. According to clinical data and bone marrow biopsy findings, patients were classified into three subgroups: adult-like myelofibrosis, pediatric immune myelofibrosis, idiopathic myelofibrosis. Pediatric Immune Myelofibrosis was the predominant subgroup in our cohort (7/14). Pediatric Immune Myelofibrosis is characterized by peculiar bone marrow features (i.e., T lymphocyte infiltration) and a milder course compared to the other patients Pediatric Immune Myelofibrosis is a novel and distinct pathological entity. We suggest to carefully consider Pediatric Immune Myelofibrosis in case of bone marrow biopsies showing myelofibrosis that do not fulfill WHO criteria.